Perubahan Sosial di Era Digital: Studi Kasus Penggunaan Artificial Intelligence (AI) di Kalangan Mahasiswa - Fuadi, Tuti Marjan; Khatimah, Husnul (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2025)
This study aims to analyze the social changes that occur among Biology Education students of Abulyatama University class of 2023 due to the use of Artificial Intelligence (AI). The study uses a case study approach with a questionnaire instrument to explore students' experiences and perceptions. The results show that 100% of participants have used AI, especially for academic purposes such as searching for references and making presentations and paper assignments. The most widely used AI are ChatGPT, Perplexity AI, Cici AI, Meta AI, Google Gemini, Google Assistant and Blackbox AI. Students benefit from the use of AI including increased productivity in terms of time and number of tasks completed but are also aware of negative impacts such as reduced social interaction and greater dependence on technology. Ethical issues also arise, highlighting the importance of critical thinking and responsible use of AI.